The Effect of Tax Planning on Firm Value: A Moderation Role of Board Diversity - Aprilliasari, Erma Dwi; Soesetio, Yuli (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2024)
This study aims to explore how tax planning practices impact firm value, with a specific focus on gender diversity as a moderating factor shaping the relationship between tax planning and firm value. Data collection involved purposive sampling, resulting in 121 samples drawn from manufacturing companies listed on the Indonesia Stock Exchange between 2018 and 2022. Employing panel data analysis supplemented by moderated regression analysis, the research uncovered several key insights. Tax planning and inflation rates exert a negative influence on firm value, whereas dividend policy and profitability have a positive impact. Interestingly, board gender diversity was found to weaken the effect of tax planning on firm value, implying that board gender diversity can significantly affect the efficacy of tax planning strategies in enhancing company value. These findings offer valuable insights for refining tax planning strategies within the manufacturing sector, considering various factors that influence firm value. Moreover, this study contributes to the existing literature on tax planning and corporate governance, laying a groundwork for further exploration and aiding in the evolution of more robust theories and frameworks in this scope.